Story line in image-based Virtual Reality for enhancing spatial presence experience - Rambli, D.R.A. (Institute of Electrical and Electronics Engineers Inc., 2014)
Presence or feel being located in virtual environment can make the Virtual Reality application more effective. One type of Virtual Reality application is Image-based Virtual Reality application; which defined as the panoramic virtual environment that mimic the real environment which users can interact with. Due to the limited interaction function, none research exists between Image-based Virtual Reality application and user's Presence experience. However, Communication Theory claims that one type of presence which is spatial presence can be experienced by users with virtual environments that match the real environment. As motivated by this theory, An exploratory study on Image-based Virtual Reality and Spatial Presence is conducted by using Repertory Grid Technique. The objective of this study is to measure the user's spatial presence experience and to identify the factors that could enhance the experience. The result revealed that IBVR application could developed user's spatial presence experience. Moreover, a few IBVR characteristics are revealed by this study. However, in this paper, the result on the story line in IBVR application is only presented. Our results suggested three features of story line in IBVR application that could create users spatial presence experience; clear story line, acceptable story line, and end-start visual of the story line. Â© 2014 IEEE.